DINAMIKA PENGELOLAAN HUTAN BERSAMA MASYARAKAT (Studi Kasus Lmdh Tani Mukti Giri Jaya, Desa Mekarmanik, Kecamatan Cimenyan, Kabupaten Bandung) - Fadil Bagaskara; Ahmad Choibar Tridakusumah (Universitas Galuh Ciamis, 2021)
Natural resource management plays an important role in supporting people's welfare. There is a joint forest management with the community through a government program that involves Perum Perhutani and the community through forest village community institutions. Based on the results of observations, LMDH Tani Mukti Giri Jaya has gone through various institutional conditions that are not working properly to internal reform of the management of the institution. The purpose of this study was to determine the dynamics of community forest management at LMDH Tani Mukti Giri Jaya at the time the institution was founded, at this time, and the institution's future plans. This research uses qualitative methods with case study techniques. The results of this study indicate that the institutional problems that occurred during the previous management have started to be addressed and are taking steps for the long-term plans of the institution. From the aspect of forest utilization, there are three main points, namely as a driving factor, impact, and constraint. The driving factor has extensive natural resources, the impact of the establishment of this institution is that forest village communities have access to use land in the Perum Perhutani area, and the obstacles of this program are often miss internal communication between institutions and farmer groups. The institutional aspect shows that LMDH coordinates with the village office and Perum Perhutani to manage the forest together with the community.